Enhanced removal of ibuprofen in water using dynamic dialysis of laccase catalysis. (June 2022) - Zhang, Jie; Cai, Qiong; Chen, Jia; Lu, Yao; Ren, Xiaolei; Liu, Qing; Wen, Li; Mateen, Muhammad
Abstract: Ibuprofen (IBU) is one of the most commonly detected active compounds in water, and its presence has raised serious concerns about the risks it poses. The dynamic dialysis of laccase catalysis (DDLC) was investigated in order to improve IBU removal from water. Laccase retention and IBU permeability were assessed during the dialysis process in order to achieve IBU removal via static laccase catalysis dialysis (SDLC). The molecular weight cut-off (MWCO) and surface area-to-volume ratio of dialysis membrane were screened by SDLC, respectively. The effects of laccase concentration, initial IBU concentration, pH, and the flow rate on IBU removal by DDLC were investigated thoroughly. In comparison to SDLC and laccase catalysis without the membrane, DDLC shows considerable advantages in improved IBU cleanup (76% IBU removal) and time efficiency. 1-isobutyl-4-vinylbenzene as the degradation product was identified by GC–MS and FTIR, and a degradation pathway involving hydroxylation, decarboxylation, and dehydration was proposed. This work represents a novelty DDLC process towards the enhancement of IBU removal using laccase. These findings provide new insights into the elimination of pollutants by enzymes and highlight the potential applications in the industrial wastewater treatment. Graphical abstract: Unlabelled Image Highlights: IBU removal is enhanced significantly by DDLC. DDLC shows considerable advantages in contaminant cleanup and time efficiency. Enzyme pollution can be eliminated by DDLC during water treatment. IBU degradation pathway catalyzed by laccase is clarified.